2012
DOI: 10.1371/journal.pone.0037643
|View full text |Cite
|
Sign up to set email alerts
|

Globalization and Loss of Plant Knowledge: Challenging the Paradigm

Abstract: The erosion of cultural knowledge and traditions as a result of globalization and migration is a commonly reported phenomenon. We compared one type of cultural knowledge about medicinal plants (number of plants reported to treat thirty common health conditions) among Dominican laypersons who self-medicate with plants and live in rural or urban areas of the Dominican Republic (DR), and those who have moved to New York City (NYC). Many plants used as medicines were popular Dominican food plants. These plants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
107
1
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 23 publications
5
107
1
9
Order By: Relevance
“…The results indicate that the health insurance system effectively works and promotes the use of more health care services. Therefore, as previous studies (Caniago & Siebert, 1998;Vandebroek & Balick, 2012) have found, it is safe to say that the health care service contributes to the decrease in medicinal plant use and knowledge, although not directly. What this study found is that indigenous people seemed to be more influenced by the health care service than the mestizo population, in turn, knowledge loss would be a concern, and too much knowledge may have already been lost.…”
Section: Commercial Medicinal Plant Productsmentioning
confidence: 81%
See 2 more Smart Citations
“…The results indicate that the health insurance system effectively works and promotes the use of more health care services. Therefore, as previous studies (Caniago & Siebert, 1998;Vandebroek & Balick, 2012) have found, it is safe to say that the health care service contributes to the decrease in medicinal plant use and knowledge, although not directly. What this study found is that indigenous people seemed to be more influenced by the health care service than the mestizo population, in turn, knowledge loss would be a concern, and too much knowledge may have already been lost.…”
Section: Commercial Medicinal Plant Productsmentioning
confidence: 81%
“…However, Aguilar--Støen and Moe (2007) report that 3.3% of medicinal plants found in studies in eight countries were cultivated species. Another aspect of NTFP studies is whether plants are used for household consumption or trade (Godoy et al, While in some developing countries medicinal plants are important in primary health care (Estomba et al, 2006;Kitula, 2007;Lozada et al, 2006;Milliken & Albert, 1997), reliance on modern medicine increases (Caniago & Siebert, 1998;Vandebroek & Balick, 2012) in other places. Choice between traditional and modern medicine depends on the users' social and cultural values with respect to each medicine (Janes, 1999;Wayland, 2004) or their knowledge of medicinal plants (Dahlber & Trygger, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pour les besoins de soins de santé primaires, l'utilisation des plantes médicinales tient encore une place de choix sur le continent. Cependant, l'accès à ces plantes utiles devient un problème croissant à cause de la dégradation progressive de la végétation naturelle et l'érosion des connaissances traditionnelles (Vandebroek et Balick, 2012 ;Malan et al, 2015). L'ethnobotanique est une discipline récente, décrite par Turner (1988) comme une science des interactions entre les humains et les plantes.…”
Section: Introductionunclassified
“…Investigation of their knowledge of medicinal plants revealed that in all three countries they abandoned specific medicinal plants and related practices from the original pharmacopeia when the plants were neither available nor cultivated in the country of arrival (Pirker et al 2012). Migrants might also actively preserve the flora and knowledge from their home country or region as an attempt to conserve their cultural identity, as for example, the case of the Dominicans living in New York City (Vandebroek and Balick 2012) or the Surinamese in the Netherlands (van Andel and Westers 2010).…”
Section: Introductionmentioning
confidence: 99%